Korelasi Motivasi Kerja dan Kompetensi Guru dengan Kinerja Guru SMA Karya Sejati Palembang - Debby Marthalia (Program Studi Magister Manajemen FE Unsri, 2018)
Tujuan penelitian - This study aimed to identify the relationship of work motivation and competence of teachers with performance. Desain/Metodologi/Pendekatan– The instrument used is a questionnaire about work motivation and competence of teachers as independent variables and questionnaires about the performance as the dependent variable. Questionnaire instruments work motivation, teacher competence and performance validated with Pearson Product Moment correlation formula (PPM), while reliability is measured by alpha cronbach instrument. Analysis of data using multiple regression analysis. Temuan– From the research found that: (1) There is a relationship between independent variables together with the dependent variable, where multiple correlation coefficient of (R) of 0.842, (2) The dependent variable can be explained by the independent variables with a contribution of 70.9%, (3) there is a relationship between work motivation with performance, there is a relationship between teacher competence with performance, but collectively have a significant relationship between work motivation and competence of teachers with senior high school teachers' performance Karya Sejati Palembang Keterbatasanpenelitian– Originality/value– Keywords: Work Motivation, Teacher Competency, Performance